Teaching Public and Population Health in Medical Education: An Evaluation Framework. (December 2020) - Johnson, Sherese B.; Fair, Malika A.; Howley, Lisa D.; Prunuske, Jacob; Cashman, Suzanne B.; Carney, Jan K.; Jarris, Yumi Shitama; Deyton, Lawrence R.; Blumenthal, Daniel; Krane, N. Kevin; Fiebach, Nicholas H.; Strelnick, Alvin H.; et al.
Abstract : Curriculum models and training activities in medical education have been markedly enhanced to prepare physicians to address the health needs of diverse populations and to advance health equity. While different teaching and experiential learning activities in the public health and population health sciences have been implemented, there is no existing framework to measure the effectiveness of public and population health (PPH) education in medical education programs. In 2015, the Association of American Medical Colleges established the Expert Panel on Public and Population Health in Medical Education, which convened 20 U.S. medical faculty members whose goal was to develop an evaluation framework adapted from the New World Kirkpatrick Model. Institutional leaders can use this framework to assess the effectiveness of PPH curricula for learners, faculty, and community partners. It may also assist institutions with identifying opportunities to improve the integration of PPH content into medical education programs. In this article, the authors present outcomes metrics and practical curricular or institutional illustrations at each Kirkpatrick training evaluation level to assist institutions with the measurement of (1) reaction to the PPH education content, (2) learning accomplished, (3) application of knowledge and skills to practice, and (4) outcomes achieved as a result of PPH education and practice. A fifth level was added to measure the benefit of PPH curricula on the health system and population health. The framework may assist with developing a locally relevant evaluation to further integrate and support PPH education at U.S. medical schools and teaching hospitals.